تحديد وسائط تعليمية لتوظيف المصطلح القرآني في تصميم الكتاب المدرسي العلمي - صالح بن طاهر مشوش (International Institute of Islamic Thought, 2018)
يدرس البحث كيفية توظيف المصطلح القرآني في محتويات الكتاب المدرسي في مادة العلوم. يقوم الإطار المرجعي لتوظيف المصطلح القرآني على بنية مفهومية-قيمية ثلاثية تضم التفكُّر والتذكُّر والشكر، وتستجلي محفزاتها المادية الخارجية (التسخير، والتقدير، والتوازن)، وتبين الرؤية النظرية الكلية التي تُسوِّغ الترتيب التصوري والمنهجي في تصميم الكتاب واستخدامه في المدرسة. يتضمن البحث ثلاثة محاور: أولها أثر الوحي في نشأة التفكير العلمي، وثانيها وسائل الوحي المعرفية في صياغة التفكير العلمي، وثالثها وظيفة المصطلح القرآني في مجال العلوم الطبيعية. وتوصل البحث إلى أن العلاقة التي تجمع الوحي مع العلوم الكونية علاقة تلازمية ضرورية، وبنائية وظيفية، وأصولية تكوينية، لا يمكن الاستغناء عنها في تشكيل ماهية العلم وترشيد تطبيقاته العملية. This work examines the way to incorporate the Qur'anic terminology in the contents of science textbooks. The Qur'anic conceptual frame is based on three core concept-values namely: thinking, remembering, and gratitude. Those values are related to specific features of the physical world, that illustrate three main features namely, (taskhir- subjection), (taqdir-quantificatin), and (mizan-balance). They also illustrate the worldview that defines the conceptual and methodological arrangement in the design and use of school textbooks. The first part of the paper deals with the impact of revelation on the emergence of scientific thinking. The second is about the cognitive means of revelation and the formulation of scientific thinking. The last part deals with function of the Quranic terminology in the field of natural sciences. The study has found that the relationship that brings revelation with natural science is a necessity, functional and constructive which can't be ignored in shaping the nature of science and using its practical applications wisely.